A Theoretical Study On The Effect Of A False Twister On The Spinning Triangle In Yarn Formation On A Ring Frame (Eurasian Journal of Engineering and Technology, 2024)
The spinning triangle is a critical aspect of the ring spinning process, where the formation of yarn occurs on the front rollers of the machine. The distribution of tension forces within the spinning triangle significantly influences the properties of the resulting spun yarn. Traditional theoretical models assume that fibre tension during yarn twisting is perpendicular to the line of intersection of the front rollers. However, this assumption may not hold when a modification device is introduced to create a false twist effect, ensuring constant fibre tension forces at the corners and sides of the spinning triangle. In this article, a novel theoretical study was conducted, considering a constant angle of fibre tension within the spinning triangle. This approach takes into account the impact of spinning parameters, the shape of the spinning triangle, and the specific angle of yarn breaking strength on the quantitative characterization of fibre tensile strength. The proposed theoretical studies aim to analyze the effects of various factors, such as different fiber masses, the number of twists, tension forces, and angles α and β within the spinning triangle. The study also introduces a modification device placed between the front rollers and the yarn guide during the ring spinning process. By incorporating the false twist effect and the constant angle of fiber tension, the theoretical framework presented in this work seeks to provide a more accurate understanding of the spinning triangle dynamics. This enhanced theoretical model enables a comprehensive analysis of how modifications to the spinning process, such as the introduction of a specific device, impact the overall tensile strength of the yarn. The findings from this study guide optimizations in ring spinning processes to achieve desired yarn properties and performance